Miesto kompozicijos sampratos klausimu - Grunskis, Tomas (Journal of Architecture and Urbanism, 2010)
About the issue of the urban composition conceptSummary A city nowadays has become a really complex and multi-layered structure containing the features of a phenomenon. It is a formation that has transformed or forced to rethinking many “standardized” urbanistic theories and approaches. By its shape and content it is a dynamic, constantly changing and multiple system related to other larger urban structures forming larger-scale urbanized networks. Due to such peculiarities, the city and its aesthetic qualities can no longer by judged and defined by the categories of the 19th and 20thcenturies. Its issues and problems have long ago trespassed the boundaries of a single scientific discipline. Nevertheless, the issue of urban aesthetics and composition still remains very relevant, especially bearing in mind recent global socio-cultural conditions and the related urban unification, as, following the intense wave of urbanization, many Lithuanian towns, with the capital Vilnius preeminently, have changed a lot, both on “the outside” (cityscape) and “the inside” (local visual perception) within the last decade. Many examples of such recently transformed towns in Lithuania just testify the fact that the issue of aesthetics and composition has been almost or totally ignored in further developing or newly shaping the centers of such towns. By exploring quite a large number of foreign and Lithuanian sources of urban theory and examples of urban space and composition analysis (these are presented in the attached bibliography), the article author aims at reviewing and analyzing the categories of urban composition, its theoretical approaches and insights. This text is a presentation of interim results of the larger research. Some thesises and concepts have been also presented in different scientific conferences and publications, in the Lithuanian and English languages.Article in Lithuanian.Santrauka. Analizuojant daug užsienio ir Lietuvos urbanistikos teorijos literatūros šaltinių ir urbanistinės erdvės (Urban Space) bei kompozicijos analizės pavyzdžių, pateikiamų šio straipsnio literatūros sąraše, apžvelgiamos ir analizuojamos urbanistinės (arba miesto) kompozicijos kategorijos, teorinės nuostatos bei sampratos. Šiame tekste pateikiami tarpiniai didesnio tyrimo rezultatai. Kai kurios jo tezės ir nuostatos buvo paskelbtos mokslinėse konferencijose bei mokslinėse publikacijose lietuvių ir anglų kalbomis.Reikšminiai žodžiai: urbanistinė kompozicija, miesto kompozicija, meniniai urbanistikos principai.First Published Online: 22 May 2013